Seismic response of multi-span simply supported bridges to a spatially varying earthquake ground motion. - Zanardo, Giovanna (Earthquake engineering & structural dynamics.)
This paper carries out a parametrical study of the pounding phenomenon associated with the seismic response of multi-span simply supported bridges with base isolation devices. In particular, the analyses focus on the causal relationship between pounding and the properties of a spatially varying earthquake ground motion. In order to include the effect of the torsional component of pounding forces on the seismic response of the whole structure, a three dimensional (3D) finite element model has been defined and 3D non-linear time history analyses have been performed. A parametrical study on the size of the gaps between adjacent bridge decks has highlighted that the pounding effects are amplified when the spatially varying ground motion time histories at each support are considered. Because of a spatially varying input, the pounding forces can assume values 3-4 times larger than those derived by a conventional seismic analysis with uniform input or with spatial input but considering ground motion wave passage effect only. The numerical results show that in order to achieve an acceptably safe structural performance during seismic events, a correct design of the isolation devices should take into account the relative displacements calculated by means of a non-linear time history analysis with multi-support excitation.